Efficient Synthesis of Isoquinolines via Rh(III)-Catalyzed Oxidative Annulation of Picolinamides with Alkynes - Qian, Zhen-Chao; Zhou, Jun; Li, Bo; Shi, Bing-Feng (Synlett, 2014)
An efficient synthesis of isoquinolines via Rh(III)-catalyzed oxidative annulation of picolinamides with alkynes using Cu(OAc)2 as an oxidant has been developed. The scope of the reaction was studied with a selection of various picolinamides and alkynes, and the desired isoquinolines were obtained in good to excellent yields.
Keywords: isoquinoline; rhodium(III); C–H activation; pyridine; oxidative annulation